2019
DOI: 10.1007/s42995-019-00007-0
|View full text |Cite
|
Sign up to set email alerts
|

Microbial diversity of sediments from an inactive hydrothermal vent field, Southwest Indian Ridge

Abstract: The Southwest Indian Ridge, which is the slowest-spreading of the main ridges, separates the African and Antarctic plates. The slow expanding rate is associated with less density of hydrothermal vent fields, shorter longevity of hydrothermal activity, cold mantle temperatures and thick lithosphere. However, the microbial communities adapting to such specific characteristics of this area have remained largely unexplored. To study the microbial diversity at the Southwest Indian Ridge, we sampled three sediment c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 75 publications
(81 reference statements)
0
18
0
Order By: Relevance
“…Following the in-depth study of hydrothermal areas, it has been reported that abundant and diverse microbial communities can be found living near hydrothermal vents [8, 9], and have close relationships with the hydrothermal animal communities, including tubeworms, shrimp, crabs and mussels. Mussel samples ( Bathymodiolus azoricus ) were collected from Tangyin hydrothermal field (station R11, 25° 0′ N, 122° 34′ E) at a depth of 1165 m in the Okinawa Trough during the cruise HOBAB4 conducted by the R/V Kexue in June 2016.…”
Section: Full-textmentioning
confidence: 99%
“…Following the in-depth study of hydrothermal areas, it has been reported that abundant and diverse microbial communities can be found living near hydrothermal vents [8, 9], and have close relationships with the hydrothermal animal communities, including tubeworms, shrimp, crabs and mussels. Mussel samples ( Bathymodiolus azoricus ) were collected from Tangyin hydrothermal field (station R11, 25° 0′ N, 122° 34′ E) at a depth of 1165 m in the Okinawa Trough during the cruise HOBAB4 conducted by the R/V Kexue in June 2016.…”
Section: Full-textmentioning
confidence: 99%
“…Previous studies have discussed vertical benthic microbial diversity in varied depth ranges (Inagaki et al, 2003, 2015; Nunoura et al, 2016, 2018; Schauer et al, 2010; Starnawski et al, 2017; Vuillemin, Vargas, et al, 2020; Vuillemin et al, 2019; Walsh et al, 2016), and highly resolved vertical profiles of microbial communities in sediments will help to better depict the stratified community structure and continuous variations in microbial diversity. However, so far, the majority of these studies have often focused on specific types of sedimentary environment (Nunoura et al, 2018; Yang et al, 2020) or comparison of microbial community over large spatial or temporal scales (Böer et al, 2009; Hoshino et al, 2020; Hoshino & Inagaki, 2019). Parallel comparison of site‐to‐site microbial diversity at different depths in a less varied sediment region is scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Diverse microbial communities are found in deep sea hydrothermal vent fields globally, including free-living and symbiotic bacteria [9]. Shrimp samples ( Alvinocaris longirostris ) were collected from the Tangyin hydrothermal field (station R11, 25° 0′ N, 122° 34′ E) at the sea water depth of 1165 m in the Okinawa Trough during the cruise ‘HOBAB4’ conducted by the R/V Kexue in June 2016 [10].…”
Section: Full-textmentioning
confidence: 99%